Neurocysticercosis as a first seizure in a 5 years old child: A case report - Chaudhary, Jenith; Niroula, Sudip (Med Phoenix, 2024)
Introduction: Neurocysticercosis (NCC) is a parasitic infection of the central nervous system caused by Taenia solium, a pig tapeworm. Humans acquired the infection via contaminated food, water, and poor hygiene. NCC has different clinical manifestations based on their location, like focal deficits, headaches, seizures, hydrocephalus, etc. Diagnosis can be made based on radio-imaging findings, supported by laboratory assays. The treatment plan includes the control of symptoms with the initiation of anti-parasitic medications, corticosteroids, and surgery as indicated based on the location of the NCC. NCC is a preventable disease, proper hygiene and sanitation, intake of properly cooked meals are helpful. Early diagnosis and early initiation of treatment play a crucial role in the management of NCC with good outcomes.